CAMINHOS DO MITO DE BENZAITEN NO TEATRO JAPONÊS: PATHS OF THE MYTH OF BENZAITEN IN JAPANESE THEATER - FONTES, Érica Rodrigues (Travessias Interativas, 2020)
RESUMO: No artigo em voga pretende-se examinar como o mito da deusa Benzaiten é apresentado na peça clássica de teatro nô Chikubushima (A ilha de Chikubu) e reapresentado na peça de teatro japonês contemporâneo Nio no umi ni te (Sobre o Lago Biwa). Além da investigação da utilização do mito nos dois trabalhos, serão examinados outros elementos semióticos nas duas peças. A análise, feita à luz dos estudos de Joseph Campbell e Mircea Eliade sobre o mito, verificará ainda se é precisamente o mito – e não os outros elementos – que impulsiona a narrativa, estabelece a estrutura da obra e, se for o caso, com que intento isso ocorre. PALAVRAS-CHAVE: Literatura. Mito. Literatura Dramática. Teatro Japonês. ABSTRACT: In the article in vogue, the aim is to examine how the myth of the goddess Benzaiten is presented in the classical noh play Chikubushima (Chibuku Island) and once again in the contemporary Japanese play Nio no umi ni te (About Lake Biwa or Happy Prince Fish, English title given by the group performing the piece). Besides investigating the utilization of the myth in both works, other semiotic elements will be examined. The analysis, made in the light of Joseph Campbell’s and Mircea Eliade’s studies about the myth will verify if it is precisely the myth – and not the other elements – which moves the narrative forward, establishes the structure of the work and, if so, with what intent it occurs. KEYWORDS: Literature. Myth. Dramatic Literature. Japanese Theater.